A Contrastive Analysis of Present Continuous Tense Formula Between Arabic and English at Senior High School Level - Budiman Budiman; Farihah Farihah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study analyzes the distinctions and commonalities in the utilization and structure of the Present Continuous Tense in Arabic and English among senior high school students. A multitude of pupils encounter challenges due to the frequent conflation of the English form with the Simple Present, particularly regarding auxiliary verbs, temporal indicators, and subject-verb concord. The mudhāri‘form in Arabic is occasionally employed to denote past or current activities, leading to potential misunderstandings when juxtaposed with English grammatical conventions. This study used a qualitative contrastive analysis method to evaluate grammatical patterns, sentence structures, and meanings conveyed in both languages. The results indicate that structural and semantic disparities result in frequent learner mistakes. The study shows that educators ought to implement contrastive teaching tactics to enhance students' comprehension of the Present Continuous and minimize errors.